Persoalan Toleransi dan Kebenaran Menjaga Agama Islam pada QS. Ali ‘Imran: 18–19 - Dini Sadiyah; Ali Hasan Assidiqi (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2023)
Tolerance is a solution to fostering harmonious interaction between mankind. In interfaith, tolerance is understood as respecting each other and not imposing will. The truth claims made by each religion allegedly fueled intolerant attitudes among religious people. The truth of Islam is based on QS. Ali Imran verse 19. This study is essential to forming a tolerant attitude among religious people when interacting. This research used a comparison method between Quraish Shihab and Ibn Katsir. The similarity between the two lies in terms of the presentation of the interpretation and the difference in the explanation of the interpretation, where Quraish Shihab is more detailed in his interpretation. Both interpret Islam as the sharia of the Prophet Muhammad Saw. According to both, tolerance is the understanding that everyone is free to choose, all can live what they believe, and there is no need to impose their will or opinions on others. One's freedom is inseparable from God's will; it is God who wills whom He gives power, all to walk based on His knowledge, wisdom, and justice.